Commodity price volatility and nutrition vulnerability - Verma, Monika; Hertel, Thomas W. (International Food Policy Research Institute, 2009)
In this paper we examine the impact of commodity price volatility on calorie attainment and its variability for households at the nutritional poverty line in Bangladesh. We focus on the first two moments of the distribution of calorie consumption and consider the differential impacts across socioeconomic groups within the country. The framework developed is then used to examine the direction and magnitude of the shift in those moments as a result of implementation of a special safeguard mechanism aimed at preventing import surges.